Effect of body mass index on latency periods after history‐indicated cervical cerclage. (8th February 2014) - Yalvac, Serdar; Esin, Sertac; Kocak, Ozgur; Yirci, Bulent; Kandemir, Omer
<x xml:space="preserve">Abstract</x> Background The impact of maternal body mass index (BMI) on cervical cerclage outcomes is not clear in the literature. Aim We sought to investigate the impact of BMI on history‐indicated cervical cerclage outcomes in our unit. Methods We retrospectively reviewed 196 history‐indicated cervical cerclage procedures. The results were analysed according to the BMI groups <25, 25–30 and ≥30 kg/m2. Results A total of 122 cases were available for the final analysis. Thirty‐two (26.1%) of the women had normal BMI (BMI < 25), 69 (56.5%) were overweight (BMI = 25–30) and 21 (17.4%) were obese (BMI ≥ 30). The mean gestational age of delivery according to BMI groups <25, 25–30 and ≥30 were 37.2 ± 3.1, 36.0 ± 5.3 and 36.0 ± 4.9 weeks (P = 0.591), respectively. The mean latency periods according to BMI groups <25, 25–30 and ≥30 were 24.3 ± 3.2, 21.1 ± 5.1 and 21.4 ± 4.9 weeks (P = 0.171), respectively. We found no correlation between the BMI and latency periods (Spearman's rho = −0.252). The multivariable logistic regression model found no variable to affect preterm birth rates. Conclusions The BMI has no impact on history‐indicated cervical cerclage procedure outcomes. Normal weight, overweight and obese women had similar latency periods after history‐indicated cervical cerclage. This high percentage of preterm birth risk necessitates close surveillance of these women for preterm birth.